Enteric tube placement in patients with esophageal varices: Risks and predictors of postinsertion gastrointestinal bleeding. Issue 2 (10th September 2019) - Al‐Obaid, Lolwa N; Bazarbashi, Ahmad Najdat; Cohen, Margot E.; Kim, Judith; Lei, Yuxiu; Axelrad, Jordan E.; Fox, Alyson; Chandra, Subani; Gordon, Fredric D.
Abstract : Background and Aim: Enteric tube (ET) placement is approached with caution in patients with esophageal varices (EV) due to concern of causing variceal bleeding. Data are limited on rates and predictors of gastrointestinal bleeding (GIB) in these patients. This study aims to assess the rate and predictors of bleeding from EV after ET placement. Methods: We performed a retrospective chart review on patients requiring ET access with known EV. Inclusion criteria were age >18 with endoscopically proven EV who required ET placement. Patients who were admitted with, or developed a GIB prior to placement of ET were excluded, as were patients admitted for liver transplantation. Primary outcome was incidence of GIB within 48 h of tube placement. Secondary outcome was a >2 g/dL drop in hemoglobin within 48 h of placement without evidence of bleed. Statistical analysis was performed using Fischer's exact test, Mann–Whitney U test, and univariate logistic regression model. Results: A total of 75 patients were included in the analysis. The most common etiology of cirrhosis was alcohol (44%). The most common location of EV was in the lower third of the esophagus (61%). The primary outcome was observed in 11 (14.6%) patients. The secondary outcome was found in eight (10.6%) patients. On univariate analysis, GIB was associated with higher MELD‐Na ( P = 0.026) and EV located in the lower third of the esophagus ( P = 0.048). Conclusion: ET placement in patients with EV is associated with low risk of bleeding. Elevated MELD‐Na and lower EV location conferred a higher risk of bleeding after ET placement. Abstract : Enteric tube placement in patients with esophageal varices (EV) is associated with low risk of bleeding. Elevated MELD‐Na and lower EV location conferred a higher risk of bleeding.